High-speed processes during pulse breakdown of vacuum gaps; Proceedings of the IVth International Conference on Phenomena in Ionized Gases, Waterloo, Ontario, september 1-4, 1970 - Litvinov E. A. (1970, 1970)
В фонде НТБ ТПУ отсутствует